Prospects for developing an early maturing variety of Winged Bean (Psophocarpus tetragonolobus) in Bogor, Indonesia - Graham Eagleton (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Eagleton GE. 2019. Prospects for developing an early maturing variety of Winged Bean (Psophocarpus tetragonolobus) in Bogor, Indonesia. Biodiversitas 20: 3142-3152. To investigate the possibility of producing a more convenient, early-maturing cultivar of winged bean for vegetable growers in West Java, an early flowering accession introduced from Singapore Botanic Gardens (‘Singha’, the female parent) was crossed with a vegetatively vigorous, late-maturing, local winged bean accession (‘Bogor’, the male parent). The phenology and general performance of plants of the parental accessions and of their F1 and F2 hybrid generations were compared in the plant nursery of the Bogor Botanic Gardens (6036’ S, 106048’ E) in three successive experiments over ten months. In each of the three experimental plantings, the mean number of days to first open flower for the Bogor variety (B) was more than 40 days later than for the Singha variety (S). There was no significant difference in the average number of days to first open flower between F1 plants (S x B) and Singha plants in the first two experiments, but in the third experiment the F1 plants flowered 23 days later than the Singha parent. The phenological development of all genotypes, but especially the Bogor variety, appeared to be retarded by long daylengths. Out of nineteen F2 plants included in the third experiment, six flowered at least as early as the average of the early flowering Singha parent, nine overlapped the distribution for the F1 plants, while only two were as late as the Bogor parent. It was inferred that flowering time in this particular cross was influenced as much by dominance effects as by additive genetic effects, with early flowering dominant to late flowering. Plants in the first two experiments were severely affected by collar-rot disease with no difference between genotypes. In the third experiment, planted in a potting-mix in poly-bags that avoided the collar-rot, all plants of the Singha and most plants of the F1 and F2 generations became infected by false-rust disease Synchytrium psophocarpi (Rac.) Baumann, whereas none of the Bogor plants exhibited symptoms of false-rust. The results support the finding in a previous study by Aminah-Lubis and Sastrapradja (1981) that the resistance to false rust disease found in Bogor winged bean varieties is conferred by genes that are recessive to genes conferring susceptibility to the disease. This investigation has implications for breeding improved varieties of vegetable winged bean and for understanding the evolution of winged bean as a crop.